The Canadian Species at Risk Act at 20: an aquatic perspective - Nicholas E. Mandrak (FACETS)
I reflect upon how successful the implementation of the Canadian Species at Risk Act (SARA), enacted in 2002, has been at meeting its intended purposes of protecting and recovering at-risk species through the implementation of the five-step SARA process, particularly as it relates to aquatic species at risk. For each one of the steps, I identify shortcomings and provide recommendations to overcome those challenges. The overall implementation of the SARA process has fallen far short of incorporating Indigenous knowledge as outlined in Act, dealt poorly with climate change, and underestimated the need for Western science at each step in the process. Addressing these challenges would require large increases in funding, as current funding is woefully inadequate to undertake current legislated requirements of SARA, let alone the aspirational goals of actually recovering species. Despite these challenges, the Act we have is better than the alternative of no Act at all and that many species have benefitted.